2011
DOI: 10.1509/jmkr.48.3.472
|View full text |Cite
|
Sign up to set email alerts
|

It's the Mind-Set that Matters: The Role of Construal Level and Message Framing in Influencing Consumer Efficacy and Conservation Behaviors

Abstract: across three studies, this research elucidates when loss-versus gainframed messages are most effective in influencing consumer recycling by examining the moderating role of whether a more concrete or abstract mind-set is activated. First, in a field study, the authors demonstrate that loss frames are more efficacious when paired with low-level, concrete mind-sets, whereas gain frames are more effective when paired with high-level, abstract mind-sets. this is an important, substantive finding that persisted ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

32
514
1
24

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 575 publications
(571 citation statements)
references
References 60 publications
(87 reference statements)
32
514
1
24
Order By: Relevance
“…For instance, De Bruijn and colleagues (2016) found that short-term consequences only changed intentions toward hearing loss prevention when combined with lossframed information. Similar effects were obtained for recycling intentions in adults (White, MacDonnell, & Dahl, 2011) and fruit intake intentions in undergraduate students (Hing Lo et al, 2012). In contrast, other research either has failed to detect an interaction between message frame and temporal context (Bernstein et al, 2016;Nan et al, 2015) or has found opposite results (Gerend & Cullen, 2008).…”
Section: Message Framing and Temporal Contextsupporting
confidence: 62%
See 3 more Smart Citations
“…For instance, De Bruijn and colleagues (2016) found that short-term consequences only changed intentions toward hearing loss prevention when combined with lossframed information. Similar effects were obtained for recycling intentions in adults (White, MacDonnell, & Dahl, 2011) and fruit intake intentions in undergraduate students (Hing Lo et al, 2012). In contrast, other research either has failed to detect an interaction between message frame and temporal context (Bernstein et al, 2016;Nan et al, 2015) or has found opposite results (Gerend & Cullen, 2008).…”
Section: Message Framing and Temporal Contextsupporting
confidence: 62%
“…That is, framing effects only occur in adolescents when losses are described in short-term outcomes (De Bruijn et al, 2016). For adults (as per the present study) lossframed (vs. gain-framed) messages can be combined with shortterm (vs. long-term) consequences to be persuasive (White et al, 2011), whereas evidence from young adult undergraduate students is mixed (Bernstein et al, 2016;Gerend & Cullen, 2008;Nan et al, 2015). More research in diverse age groups is therefore needed to better understand message framing and temporal context effects.…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…Monitoring and apportionment of energy consumption enable the setting of goals for reduced consumption, which can have an important motivational effect on individuals and groups (Davis 1995;White, MacDonnell, and Dahl 2011). Goal setting promotes action by directing people's attention and effort towards the goal; through energising people to try to achieve the goal; through encouraging persistence in behaviours that work towards the goal and by making salient and encouraging the discovery of new goal-relevant information and strategies (Locke and Latham 2002).…”
Section: Apportioning Consumption To Occupantsmentioning
confidence: 99%